Analyses of electron runaway in front of the negative streamer channel. Issue 8 (29th August 2017) - Babich, L. P.; Bochkov, E. I.; Kutsyk, I. M.; Neubert, T.; Chanrion, O.
Abstract: X‐ray and γ‐ray emissions, observed in correlation with negative leaders of lightning and long sparks of high‐voltage laboratory experiments, are conventionally connected with the bremsstrahlung of high‐energy runaway electrons (REs). Here we extend a focusing mechanism, analyzed in our previous paper, which allows the electric field to reach magnitudes, required for a generation of significant RE fluxes and associated bremsstrahlung, when the ionization wave propagates in a narrow, ionized channel created by a previous streamer. Under such conditions we compute the production rate of REs per unit streamer length as a function of the streamer velocity and predict that, once a streamer is formed with the electric field capable of producing REs ahead of the streamer front, the ionization induced by the REs is capable of creating an ionized channel that allows for self‐sustained propagation of the RE‐emitting ionization wave independent of the initial electron concentration. Thus, the streamer coronas of the leaders are probable sources of REs producing the observed high‐energy radiation. To prove these predictions, new simulations are planned, which would show explicitly that the preionization in front of the channel via REs will lead to the ionization wave propagation self‐consistent with RE generation. Key Points: Focusing of the ionization wave, propagating along a trail of a previous streamer allows the electric field intensity to reach magnitudes required for a generation of significant numbers of runaway electrons (REs) The ionization produced by the REs creates an ionized channel that allows for the ionization wave propagation self‐sustained with the RE generation independent of the initial electron concentration ahead of the wave front Streamer coronas of the leaders are sources of REs producing the observed X‐ray and γ‐ray emissions Plain Language Summary: X‐ray and γ‐ray emissions, observed in correlation with the negative leaders of lightning and long sparks of high‐voltage laboratory experiments, are conventionally connected with the bremsstrahlung of high‐energy runaway electrons (REs). Here we extend a focusing mechanism, analyzed in our previous paper, which allows the electric field to reach magnitudes, required for a generation of significant RE fluxes and associated bremsstrahlung, when the ionization wave propagates in a narrow, ionized channel created by a previous streamer. Under such conditions we compute the production rate of REs per unit streamer length as a function of the streamer velocity and find that, once a streamer is formed with the electric field capable of producing REs ahead of the streamer front, the ionization induced by the REs creates an ionized channel that allows for self‐sustained propagation of the RE‐emitting ionization wave independent of the initial electron concentration. Thus, the streamer coronas of the leaders are probable sources of REs producing the observed high‐energy radiation.